Anthocyanins from fruit juices improve the antioxidant status of healthy young female volunteers without affecting anti-inflammatory parameters: results from the randomised, double-blind, placebo-controlled, cross-over ANTHONIA (ANTHOcyanins in Nutrition Investigation Alliance) study. Issue 6 (28th September 2014) - Kuntz, Sabine; Kunz, Clemens; Herrmann, Johannes; Borsch, Christian H.; Abel, Georg; Fröhling, Bettina; Dietrich, Helmut; Rudloff, Silvia
<x content-type="archive" xml:space="preserve">Abstract</x> Anthocyanins (ACN) can exert beneficial health effects not only through their antioxidative potential but also through modulation of inflammatory parameters that play a major role in CVD. A randomised cross-over study was carried out to investigate the effects of ACN-rich beverage ingestion on oxidation- and inflammation-related parameters in thirty healthy female volunteers. The participants consumed 330 ml of beverages (placebo, juice and smoothie with 8·9 (sd 0·3), 983·7 (sd 37) and 840·9 (sd 10) mg/l ACN, respectively) over 14 d. Before and after each intervention, blood and 24 h urine samples were collected. Plasma superoxide dismutase (SOD) and catalase activities increased significantly after ACN-rich beverage ingestion (P< 0·001), whereas after placebo juice ingestion no increase could be observed. Plasma glutathione peroxidase and erythrocyte SOD activities were not affected. An increase in Trolox equivalent antioxidant capacity could also be observed after juice (P< 0·001) and smoothie (P< 0·01) ingestion. The plasma and urinary concentrations of malondialdehyde decreased after ACN-rich beverage ingestion (P< 0·001), whereas those of 8-OH-2-deoxyguanosine as well as inflammation-related parameters (IL-2, -6, -8 and -10, C-reactive peptide, soluble cluster of differentiation 40 ligand, TNF-α, monocyte chemoattractant protein-1 and soluble cell adhesion molecules) were not affected. Thus, ingestion of ACN-rich beverages improves antioxidant enzyme activities and plasma antioxidant capacity, thus protecting the body against oxidative stress, a hallmark of ongoing atherosclerosis.